Congress, the Supreme Court, and religious liberty the case of City of Boerne v. Flores - Waltman, Jerold; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
In the case City of Boerne v. Flores, the Supreme Court struck down the Religious Freedom Restoration Act of 1993. Waltman offers the first book-length analysis of the act to show how this case contributes to an intense legal debate still ongoing today: Can and should the Supreme Court be the exclusive interpreter of the Constitution?
Keywords: Religion; Religion and sociology; Political science; Europe -- Politics and government; Law -- Philosophy; Law; Human rights; Religious Studies; Social Aspects of Religion; European Politics; Political Science; Theories of Law, Philosophy of Law, Legal History; Human Rights; Religion and Society